DIFFERENCES IN TAMARIND, KANDIS ACID, AND STARFRUIT MORDANTS IN THE EFFECT OF DYEING KEDONDONG PAGAR (LANNEA NIGRITANA) BARK EXTRACT ON COTTON FABRIC - Yesikaberli Yesikaberli; Adriani Adriani (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The retentiveness of the color is influenced by the mordant. Mordant can be an corrosive. This ponder points to portray the contrast in mordant on the comes about of coloring kedondong pagar bark extricate on cotton fabric. This sort of investigate is exploratory inquire about. This consider employments essential information determined from 15 panelists, analyzed by the Friedman K-related Test test with the Factual Item and Benefit Arrangement application. The results of dyeing with tamarind mordant produced Clam Shell Pink color #D2AAA0. The color lightness is quite bright. Washing resistance in the first and second washes, the color has no change at all; in the third wash, the color changes slightly or decreases. The result of dyeing with the kandis acid mordant produces Clam Shell Pink color #E1B19F. The light darkness of the color is very bright. Washing resistance in the first and second washings, the color changes or decreases slightly; in the third washing, the color is seen to change or decrease. The result of dyeing with belimbing wuluh mordant produces warm brown color #D3A599. Light dark color. Washing resistance: in the first wash, the color has no change at all; in the second wash and the third wash, the color changes slightly or decreases. The comes about of the investigation of the Friedman K-related Test test for dim light color with the result that Hₐ is acknowledged and H0 is rejected, meaning there's a noteworthy distinction. washing resistance with the result that Hₐ is acknowledged and H₀ is rejected, meaning there's a noteworthy contrast. It can be concluded that there is a difference in the mordant of tamarind, kandis acid, and starfruit on the dyeing of kedondong pagar bark extract.